Translation of Cultural References in the English Subtitles of Nussa Short Movie Special Edition: ‘Kamu… Antta’ - Safi'i, Muhamad; Panggabean, Hanna Maria; Losi, Rizky Vita; Harahap, Ahmad Fadli; Siregar, Try Mahendra (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2026)
This study aims to identify and analyze the translation strategies used in translating culture-specific items (CSIs) from Indonesian into English subtitles in the Nussa short movie special edition titled "Kamu… Antta." The study applied Pedersen’s (2011) typology of translation strategies for CSIs as its main theoretical framework. The data consists of 19 Indonesian cultural terms found in the film’s dialogues, analyzed using strategies such as retention, specification, direct translation, generalization, substitution, omission, and official equivalent. The findings reveal that the most dominant strategy is generalization, followed by retention. The choice of strategies appears to be influenced by ideological and technical factors, including the purpose of translation, subtitle space constraints, and international viewers’ familiarity with Islamic and Indonesian cultural concepts. This study contributes to the field of audiovisual translation by highlighting the challenges and approaches in translating local cultural elements into a global context.‎